Prevalence and Viral Loads of Cutaneous Human Polyomaviruses in the Skin of Patients With Chronic Inflammatory Skin Diseases. (23rd October 2018) - Hashida, Yumiko; Higuchi, Tomonori; Tanaka, Moe; Shibata, Yuka; Nakajima, Kimiko; Sano, Shigetoshi; Daibata, Masanori
Abstract : This study documents changes in the infection levels of skin-residing polyomaviruses (Merkel cell polyomavirus, human polyomavirus 6, and human polyomavirus 7) on the skin of patients with long-lasting inflammation. Abstract: Background: Human skin microorganisms have been associated with various skin diseases. However, most studies have focused on bacterial communities, and little is known about normally resident skin viruses such as the Polyomaviridae and their association with cutaneous disorders. Methods: We investigated the infection levels of Merkel cell polyomavirus (MCPyV), human polyomavirus 6 (HPyV6), and human polyomavirus 7 (HPyV7), using triplet skin swabs collected from lesional and nonlesional skins of 86 Japanese patients with inflammatory skin diseases and mycosis fungoides, and from 149 healthy control individuals. Results: This age-matched case-control study provides the first analyses of the loads of polyomaviruses in association with various skin diseases. The viral loads were significantly higher for HPyV6/HPyV7 and lower for MCPyV in patients with psoriasis. The viral load variation was observed not only at lesion sites, but also at clinically unaffected skin sites in most of the patients. The viral strains tested were all of the Asian/Japanese genotype. Conclusions: Our findings suggest a covariation in the infection levels of cutaneous polyomaviruses in certain inflammatory skin conditions. Worldwide prospective longitudinal studies are warranted to understand the influence of such alterations on the pathogenesis of inflammatory skin disorders.